The Impact of Diabetes Mellitus on Cardiovascular Health - S. G’., Elmurodova; O. A., Nurmatov; K. S., Pulatova (Journal of Science in Medicine and Life, 2024)
Diabetes mellitus (DM) is one of the most prevalent metabolic disorders globally, characterized by chronic hyperglycemia resulting from defects in insulin secretion, insulin action, or both. This study aims to evaluate the effects of DM on cardiovascular health and to highlight the preventive measures and therapeutic strategies. Our findings indicate that uncontrolled diabetes significantly increases the risk of cardiovascular complications, including myocardial infarction, stroke, and heart failure. Early detection and glycemic control play pivotal roles in mitigating these risks.